Pigeonpea (Cajanus cajan) research in India-an overview - Ahlawat, I.P.S; Gangaiah, B; Singh, I (The Indian Journal of Agricultural Sciences, 2005)
Pigeonpea [Cajanus cajan (L.) Millsp.] in India had a low compound growth rate of 0.8% in production between 1949-50 and 2004 due to various biotic and abiotic stresses. Suitable management technologies to offset adverse effects of abiotic stresses like waterlogging and drought have been developed. Soil fertility is another abiotic stress for which integrated plant nutrient-management system has been evolved to enhance pigeonpea productivity in pigeonpea-based cropping systems. The threatening sustainability in cereal-based cropping systems in North-west plains Zone, flood menace in North-east Plains Zone and lower productivity of urdbean or blackgram [Vigna mungo (L.) Hepper] in utera [sowing in standing rice (Oryza sativa L.) crop] cropping have made way for pigeonpea-wheat (Triticum aestivum L. emend. Fiori & Paol.), maize (Zea mays L.)-pre-winter pigeonpea and rice (Oryza sativa L.)-pigeonpea cropping systems. The development of about 80 high-yielding, disease-resistant varieties and hybrids suitable for different situations has helped in improving not only productivity but also addressing various biotic and abiotic stresses. Resistant sources have been identified for the diseases like wilt (Fusarium udum Butler), sterility mosaic virus, blight (Phytophthora drechsleri Tucker f sp cajani Pal, Grewal & Sarabhoy) and Alternaria blight [Alternaria alternata (Fr.) Keissler], and pests such as pod-borer (Helicoverpa armigera Hubner), pod fly (Melanagromyza obtusa Malloch) and nematodes, and are being utilized in breeding programme. The development of pod-borer transgenic by the International Crops Research Institute for the Semi-Arid Tropics, Patancheru, Andhra Pradesh, would promote pigeonpea in traditional and non-traditional areas. Effective cultural and herbicidal methods of weed control to minimize losses by weeds, and also control methods to minimize losses by storage pests especially bruchids have also been developed. Processes of dal making developed at the Central Food Technology Research Institute and at Pantnagar have shown promise in minimizing the milling losses in traditional milling. Effective procurement, attractive minimum support price coupled with enhanced productivity would promote pigeonpea cultivation in green revolution tracts. The paper deals with the progress made on various aspects of pigeonpea production besides highlighting the future research thrusts.